Recent onset mental illness severity: pilot study on the role of cognition, sensory modulation, and daily life participation - Lipskaya-Velikovsky, Lena; Hershkovitz, Ayelet; Bukai, Mira; Bar-Shalita, Tami (Frontiers in Psychiatry, 2024)
Introduction: Early detection of individuals at risk for onset of severe illness is crucial for prevention and early intervention, aiming to mitigate the long-term impact on both the individual and the community. While well-established models exist for predicting the onset and prolonged severity of illness, there is a gap in understanding illness-onset severity. This pilot study aimed to investigate premorbid objective and subjective dimensions of participation in daily life occupations, as well as sensory and cognitive functions as potential markers of the recent-onset mental illness severity. Methods: A total of 50 participants (men: N=26, 52%; women: N=24, 48%), aged 18–40 (M=26.2, SD=5.8) with recent-onset mental illness completed standard, well-established assessments of illness severity, cognitive biases and failures, neurocognitive status, participation in daily life, and sensory responsiveness thorough cross-sectional design. The differences between the groups of the illness severity were explored with descriptive statistics, followed by a Kruskal–Wallis test. Discriminant analysis was used suggesting a multi-varied model for the separation between the groups of illness severity. Results: Three groups of illness severity exhibited differences in premorbid cognitive functions (F(2)=5.8, p<.01) and participation diversity (F(2)=3.8, p<.05). Combining these two indices explained 92% of the variance between the groups (Wilks’ Λ = .68, χ2(4) = 17.7, p=.001), accurately classifying mild to marked illness severity (62.5–88.5%). Conclusions: The study contributes to revealing factors involved in the formation of more severe mental illness and suggesting possible avenues for early intervention and prevention. Cognitive biases and sensory modulation dysfunction may contribute to the illness formation. Still, the most effective markers of more severe mental illness onset are functional cognition and limited participation diversity. Since addressing these markers is a unique specialization within occupational therapy, the findings highlight the potential contribution the profession can make to the early identification of the most vulnerable populations.